"I like the sound of that!" Wine descriptions influence consumers' expectations, liking, emotions and willingness to pay for Australian white wines. (September 2017) - Danner, Lukas; Johnson, Trent E.; Ristic, Renata; Meiselman, Herbert L.; Bastian, Susan E.P.
Abstract: This study investigated how information, typically presented on wine back-labels or wine company websites, influences consumers' expected liking, informed liking, wine-evoked emotions and willingness to pay for Australian white wines. Regular white wine consumers (n = 126) evaluated the same set of three commercially available white wines (mono-varietal Chardonnay, Riesling, Sauvignon Blanc) under three information levels. Session 1, blind tasting (no information provided) and Session 2, informed tasting (held at least 1 week later) with both basic (sensory description of the wines) and elaborate (sensory plus high wine quality and favourable winery information) descriptions followed by liking, wine-evoked emotions (measured with the Australian Wine Evoked Emotions Lexicon (AWEEL)) and willingness to pay evaluations. Before tasting the wine in session 2, consumers also rated expected liking. Results showed that information level had a significant effect on all investigated variables. The elaborate information level evoked higher expectations before tasting the wines, plus resulted in higher liking ratings, elicitation of more intense positive (e.g. contented, happy and warm-hearted ) and less intense negative emotions (e.g. embarrassed and unfulfilled ), and a substantial increase in willingness to pay after tasting the wines compared to the blind condition, with the basic condition ranging in-between. These results were consistent across the three wine samples. Furthermore, if the liking rating after tasting the wines matched the expected liking or exceeded the expectations by 1 point on a 9-point hedonic scale, participants felt the most intense positive emotions and the least intense negative emotions. Whereas, if the expectations were not met or the actual liking exceeded the expectations by > 2 points, participants felt less intense positive and more intense negative emotions. This highlights not only the importance of well written and accurate wine descriptions, but also that information can influence consumers' wine drinking experience and behaviour. Graphical abstract: Highlights: Three white wines were tasted under three different information conditions. Information influenced consumers' emotions, liking and willingness-to-pay (WTP). Elaborate information resulted in highest liking, WTP and positive emotions. Hedonic disconfirmation strongly influenced emotion profiles.